Islamic Guidance Counseling Services with Dhikr Practice To Increase Student Learning Motivation - Fitrila, Najima; Safitri, Arini; Ajahra, Putriani (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2024)
The aim of this research is to identify Islamic guidance and counseling services with the practice of dhikr in increasing students’ learning motivation. Based on preliminary data from observations and interviews conducted, there were students who experienced a decrease in learning motivation, which was characterized by cases of absenteeism, lateness and lack of enthusiasm in participating in class learning. This research used mixed method (quantitative and qualitative methods) and the research design used was a single case experimental which was analyzed using SPSS 24 for windows. The samples were 79 students of grade X MAN Palangka Raya who fill out pre-test questionnaires using non-probability sampling with quota sampling technique, and the subjects obtained were 6 students who included scores in the low motivation category. The average result of pre-test before being treated was 46.83 and after treating in the form of counselling guidance services through dhikr habit, it was 69. So, if the difference total score between pre-test and post-test was calculated, it would obtained a score of 22.17 which was considered as data result of improving students learning motivation. Based on the result of effectiveness test in implementing of Islamic counselling guidance services to improve students’ learning motivation at grade X MAN Palangka Raya through t-test paired sample technique, the t-test was 19,00 (sig-0,000). It can be concluded that implementation of Islamic counselling guidance services through dhikr habit effectively improve students’ learning motivation at grade X MAN Palangka raya and the score was 22,17.